PERBANDINGAN TULISAN ANTARA MAHASISWA ASING KELAS INDONESIA 2 DAN INDONESIA 5 DALAM PENULISAN BAHASA INDONESIA - Julfiyatun, Rossa; Setiawan, Arif (Jurnal Semantik, 2025)
Ho Chi Minh City Open University, one of the educational institutions in Vietnam, offers Indonesian language learning programs for foreign students with various proficiency levels. Learning Indonesian at this institution includes four language skills: speaking, listening, reading, and writing. This research aims to describe Indonesian language errors in written form by foreign students. This research is a descriptive type of qualitative research. The data contained in this research are words, phrases, clauses, and sentences in the writing of BIPA students in Indonesian class 2 and Indonesian class 5 at Ho Chi Minh Open University Vietnam. The data in this research was obtained during the teaching process as an Indonesian language teaching assistant at Ho Chi Minh City Open University, Vietnam. The data analysis technique in this research uses interactive analysis techniques by Miles & Huberman. The data analysis results found 16 writing error data in Indonesian consisting of 4 word errors, 4 phrase errors, 4 clause errors, and 4 sentence structure errors.